(untitled) (Research, Society and Development, 2022)
Introduction: Human trafficking is one of the most profitable illegal sources in the world, moving about 2.5 million people and more than US 32 billion per year. Nurses are essential for identifying trafficked persons, promoting health, and developing and implementing public policies. Objective: To analyze the assistance provided and the preparation of nurses in the care of victims of trafficking in persons at the Primary Care level. Method: This is an integrative review. Its development was based on the following guiding question: “Are nursing professionals trained to prevent, identify and assist victims of human trafficking?”. PubMed, Science Direct, SciELO and Springer databases were used. Results: 8 articles were selected for the composition of this research. that victims of human trafficking receive health care, whether in urgent and emergency centers, outpatient clinics or in the scope of primary care, however, the lack of preparation of professionals in the health system results in inadequate care for these victims, since there are a lack of training and education on trafficking that assists in the identification and holistic care of these individuals. Conclusion: The results express the lack of training of professionals to recognize the trafficked individual, as well as the need for comprehensive care in care, and highlight the importance of primary care as a fundamental part of this process.